2015
DOI: 10.5001/omj.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines Use During Pregnancy: A Review from the Middle East

Abstract: The prevalence of the herbal medicines use is on the rise across the world, especially amongst pregnant women. The scenario in the Middle Eastern region was reviewed to explore the prevalence, usage pattern, motivation, and attitude towards use of herbal medicine by pregnant women. Literature published up to December 2012 showed the prevalence of herbal medicine use varied between 22.3-82.3%, implying a rising trend in the utilization of herbal medicine during pregnancy. The most common herbs used were pepperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
138
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 28 publications
20
138
0
3
Order By: Relevance
“…The most widely used herbs include garlic, St. John’s wort, ginger, ginseng, Echinacea, kava and devil’s claw [2, 3]. These herbs are commonly used by pregnant women to relieve various complaints they experience during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widely used herbs include garlic, St. John’s wort, ginger, ginseng, Echinacea, kava and devil’s claw [2, 3]. These herbs are commonly used by pregnant women to relieve various complaints they experience during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A review study that investigated this practice in nine Middle Eastern countries found that the prevalence of herbal medication use during pregnancy ranged from 22.3% to 82.3% and that the most commonly used herbs included peppermint, ginger, thyme chamomile, sage, aniseeds, fenugreek, green tea, and garlic [3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncompliance to medications and treatment plans is not uncommon among pregnant women which might be gauged by concerns related to fetus health 11 . However, herbal or complementary medicine tends to be more accepted as they are perceived to be a safer option although they might be not 12 . Hence, this systematic review aims at investigating the efficacy of ginger in relieving NVP.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women should also be educated to increase their awareness regarding the effects of herbal/traditional medications and the importance of taking guidance from their healthcare provider/expert. 30 Volatile oil containing drugs can be abortifacient, irritant to genitourinary tract (can cause uterine contractions) example, Artimisia absinthium (thujone), Apium graveolans, Anemone pulsatilla Eucalyptus globulas (cineol) Juniperous communis (alpha & beta Pinene). Some other constituents also got uteroactivity, pyrrolizidine alkaloids can cause hepatotoxicity in a new born it is present in borage officinalis and other species, some are toxic drugs podophyllin is a mitotic poison in podophyllum hexandrum.…”
mentioning
confidence: 99%